2015
DOI: 10.1097/prs.0000000000001377
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Free Fasciocutaneous Flap Complications

Abstract: The implications of these findings can be used to contain cost and minimize poor outcomes within the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The transfer distance of the skin flaps was large, and flap sizes may have been much larger than the angiosomes perfused by a perforating artery. Furthermore, our result is consistent with that of Reece et al , who found that soft tissue defect site was a risk factor for flap necrosis …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The transfer distance of the skin flaps was large, and flap sizes may have been much larger than the angiosomes perfused by a perforating artery. Furthermore, our result is consistent with that of Reece et al , who found that soft tissue defect site was a risk factor for flap necrosis …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our result is consistent with that of Reece et al, who found that soft tissue defect site was a risk factor for flap necrosis. 25 Flap size was the second identified risk factor. Flap necrosis typically occurs in the 'choke' zone connecting the adjacent perforator angiosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in addition, Sanati-Mehrizy et al (4) reported that smoking and operation time are risk factors for free flap necrosis and de Blacam et al (7) found that venous congestion and increased age are risk factors for pedicle flap failure. Current literature regarding the risk factors of skin flap necrosis mainly focus on free skin flaps and lower limb pedicled skin flaps (8)(9)(10)(11)(12)(13)(14)(15), and treatment methods that have been proposed are based on various mechanisms such as surgical delay, chemical delay, extracorporeal shock wave therapy, local thermal pretreatment, percutaneous neuroelectric pretreatment, cold pretreatment, negative pressure suction, targeted gene therapy, and drug injection (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Heat shock proteins (Hsps), which are highly evolutionarily conserved from prokaryotes to human (26), are molecular chaperons that exhibit a variety of biological activities including anti-oxidative, anti-apoptotic and anti-inflammatory effects (27).…”
Section: Introductionmentioning
confidence: 99%